(untitled) (Indian Journal of Animal Production and Management, 2025)
Background The world-wide poultry industry has grown rapidly to provide the increasing demand for low-cost protein. This expansion offers more opportunities for zoonotic diseases to be transmitted, especially Salmonella spp. and Vibrio cholerae that are important pathogens for foodborne illness. Both Salmonella has been reported among poultry flocks in Karbala, Iraq and V. cholerae which is commonly associated with contaminated water may also represent potential zoonotic risk within the settings of poultry production. Culture-based detection is time-consuming, laborious and may fail to detect low levels of contamination; molecular methods like the polymerase chain reaction (PCR) provide fast, sensitive and specific identification of targets that are amenable for large epidemiological surveys. Objective: To investigate the molecular prevalence of Salmonella spp. and Vibrio cholerae in the different samples, their concurrent occurrence, assess associated risk factors and estimate the performance of duplex PCR assay for pathogens monitoring. Methods: Descriptive study of 20 poultry farms in Karbala province was conducted over a period of one year. In total, 82 samples were collected from the hens and cloaca swabs of poultry and feces samples (n = 82) and environmental/water (n = 118). Isolation and detection of Salmonella was based on invA gene and V. cholerae using rtxA/lolB genes by duplex PCR; results were confirmed through agarose gel electrophoresis. Chi-squared tests and logistic regression were used to determine prevalence and associations with potential risk factors, including farm biosecurity and quality of water source. Results: Salmonella spp. was found in 15% of poultry, mainly in cloacal swab indicating extensive carrier status. Vibrio cholerae was detected in 9% of water/ environment samples. Simultaneous presentation of both pathogens was found in 6% of waterborne samples, indicating possible cross-contamination predominately from water. Pathogen occurrence was positively correlated with low biosecurity and use of natural water sources (P < 0.05). The duplex PCR showed excellent sensitivity and specificity to rapid diagnosis. Conclusion: This study provides valuable molecular epidemiological evidence regarding the prevalence and cross-resistance of Salmonella and V. cholerae in Karbala region. The biosecurity and water management should be strengthened, and routine surveillance with duplex PCR is needed to prevent resistance zoonotic risks and public health protection. Serotyping of Salmonella and determination of V. cholerae toxicity need to be added in future studies to further assess public health risks.